1999
DOI: 10.1023/a:1006214830854
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in the first year after breast cancer surgery: rehabilitation needs and patterns of recovery

Abstract: At one year after surgery, most women report high levels of functioning and QOL, with no relationship between the type of surgery and QOL. Women who reported lower levels of QOL at one year after diagnosis had greater mood disturbance and poorer body image one month after surgery, as well as lower income and positive axillary nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
134
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(161 citation statements)
references
References 61 publications
21
134
0
4
Order By: Relevance
“…This hypothesis was developed from the results of our earlier study [17]. The current analysis was conducted as a multicenter longitudinal study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This hypothesis was developed from the results of our earlier study [17]. The current analysis was conducted as a multicenter longitudinal study.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we developed a list of symptoms related to disease and treatment and collected these data in a structured interview [17]. In the current study, this list was translated into …”
Section: Patient-reported Symptom Check Listmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain and physical sensations: We used 14 items from a previous study of breast cancer survivors (35) assessing the frequency of pain and physical sensations (e.g., numbness, tenderness, pins and needles) during the last three months in the chest wall or breast (7 items) and in the arms (7 items). Factor analysis revealed the chest wall/breast and arm questions grouped into two separate scales with adequate internal consistency for each (Cronbach's alphas = 0.81 and 0.88, respectively).…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Axillary lymph node dissection (ALND) in breast cancer patients still represents the routine surgical method for axillary staging. Although the axillary node status is the most important prognostic factor for recurrence and survival (Fisher et al, 1984;Carter et al, 1989) and information obtained by axillary dissection is useful for planning adjuvant treatment, it is associated with substantial morbidity (Kissin et al, 1986;Ivens et al, 1992;Keramopoulos et al, 1993;Hack et al, 1999;Kakuda et al, 1999) and psychological distress (Maunsell et al, 1993;Tobin et al, 1993;Shimozuma et al, 1999). Hack et al, showed arm/shoulder pain, weakness or numbness in 72% and impaired range of motion in 73% of breast cancer patients after ALND, whereas high levels of quality of life (QOL) were reported.…”
mentioning
confidence: 99%